Prognostic Significance of P16 Expression and P53 Expression in Primary Vaginal Cancer. (November 2019) - Nwachukwu, Chika R.; Harris, Jeremy P.; Chin, Alex; Von Eyben, Rie; Giaretta, Stephanie; Shaffer, Jenny L.; Hiniker, Susan M.; Kapp, Daniel S.; Folkins, Ann K.; Kidd, Elizabeth A.
Abstract : To evaluate the correlation between p16 expression and clinical outcomes in patients with primary vaginal cancer treated with definitive radiotherapy. P16 immunohistochemical was performed on 25 patient samples and recorded from pathology reports in 7 patients. P53 immunohistochemical was performed on 3 p16-negative samples. Baseline characteristics were compared using the Fisher exact test. Outcomes were compared using log-rank tests, and cox proportional hazards models. Survival and recurrence analysis was performed with the Kaplan-Meier method and cumulative incidence estimates. P16 expression was positive in 29 patients and negative in 3 patients. Two of the p16-negative tumors showed positive expression of p53. The median overall survival, progression-free survival and 2-yr cumulative incidence of recurrence were 66 mo [95% confidence interval (CI), 31–96], 34 mo (95% CI, 21–86), and 19% (95% CI, 7%–34%), respectively. P16-positive tumors had higher median overall survival and progression-free survival compared with p16-negative tumors (82 vs. 31 mo, P =0.02 and 35 vs 16 mo, P =0.04, respectively). The 2-yr cumulative incidence of recurrence was 14% for p16-positive tumors compared with 67% for p16-negative tumors ( P =0.07). On univariable analysis, p16-negative status, age older than 65, and advanced stage were associated with inferior overall survival. P16 negativity is an independent predictor of inferior overall survival. P16-positive vaginal cancers have a better prognosis and decreased incidence of recurrence compared with p16-negative tumors. These prognostic findings associated with p16-negative vaginal cancers will need to be confirmed in larger patient cohorts. Abstract : Supplemental Digital Content is available in the text.